“We Dare Entertain Thoughts not to the Liking of Present-Day Bigots”: Radical Slavs, Race, Civil Rights, and Anti-Communism in Red-Scare America - Zecker, Robert (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2014)
Developing a white identity was a key component in immigrants’ acculturation to America. Many immigrants learned to distance themselves from black fellow workers through cultural productions that delineated blacks as impermissible outsiders, and made a case for Slavic or Mediterranean inclusion in the Caucasian republic. Yet “red” immigrants resisted white privilege. During the 1930s-1950s, members of the International Workers Order endorsed anti-colonial movements and civil rights for blacks at home. The Slovak Workers Order and other IWO lodges joined the “American Crusade Against Lynching” and lobbied for an end to the poll tax and segregation. During World War II the IWO was active in anti-lynching and anti-poll-tax campaigns. While in the 1940s many white Americans violently resisted black attempts to integrate neighbourhoods, the radical groups sought to counter the hegemonic white narrative and build cross-racial alliances while preserving members’ discreet, ethnic identities. In no small measure because of this anti-racist activism, the Order was placed on the Attorney General’s List of Subversive Organizations. By 1954 the Order was dismantled, but for a brief moment some “red” members opted out of racial privilege in favour of black-white solidarity.